2017
DOI: 10.1038/s41598-017-08262-w
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Placement of Iliosacral Screws Under the Guidance of Axial View Projection of the S1 Pedicle: a Case Series

Abstract: The aim of this study was to evaluate the safety and efficacy of percutaneous placement of iliosacral screws under the guidance of axial view projection of the S1 pedicle clinically. This case series includes 58 consecutive unstable pelvic injury patients, which were treated with iliosacral screws between July 2011 and July 2016. Patients were divided into two groups: normal sacrum (n = 31) and dysmorphic sacrum (n = 27). A single orthopedic surgeon operated on all patients, with percutaneous placement of ilio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[12] Average fluoroscopy time per screw for standard iliosacral screw placement varies between 1.8 and 7.3 min, [1,2] and average operating time per screw has been reported between 16 and 75 min. [18,21,31,35] Two fluoroscopes' simultaneous use was reported to provide a faster approach with less exposure to radiation for percutaneous iliosacral screw placement. [21] Yin et al [31] studied the percutaneous placement of iliosacral screws under the axial view projection of the S1 pedicle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Average fluoroscopy time per screw for standard iliosacral screw placement varies between 1.8 and 7.3 min, [1,2] and average operating time per screw has been reported between 16 and 75 min. [18,21,31,35] Two fluoroscopes' simultaneous use was reported to provide a faster approach with less exposure to radiation for percutaneous iliosacral screw placement. [21] Yin et al [31] studied the percutaneous placement of iliosacral screws under the axial view projection of the S1 pedicle.…”
Section: Discussionmentioning
confidence: 99%
“…[18,21,31,35] Two fluoroscopes' simultaneous use was reported to provide a faster approach with less exposure to radiation for percutaneous iliosacral screw placement. [21] Yin et al [31] studied the percutaneous placement of iliosacral screws under the axial view projection of the S1 pedicle. ey found that the median duration from the start of preparation to the first screw insertion was 14 ± 5 min and the respective radiation exposure times were 50 ± 9 s. [31] Our study measured a fluoroscopic time of 108 ± 12 s per screw and an operating time of 21.18 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the lack of a control group and lack of biomechanical comparison is another limitation of our study. [2]…”
Section: Discussionmentioning
confidence: 99%
“…15). Generally, the length of the sacroiliac screw was no more than 2-thirds of the transverse diameter of the vertebral body in the antero-posterior view; [2] the body and the tip of sacroiliac screws were located in the cortical bone. The accuracy of navigation was checked preoperatively to confirm the normal functionality.…”
Section: Methodsmentioning
confidence: 99%